Hubungan Empati dengan Perilaku Prososial Anak Usia Dini - Sera Lapanda; Ari Sofia; Rizky Drupadi (incrementapedia, 2022)
This study aims to determine the relationship between empathy and prosocial behavior of children aged 5-6 years. Researchers used quantitative research. The research sample was taken using a saturated sample of 25 children aged 5-6 years in Ra Maarif Watas. Data collection ini this study was conducted by observation and documentation. The data was proceed Spearman rank correlation analysis. The result showed that there was a relationship between empathy and prosocial behavior in children. This is evident from rcalculate 0.771> rtable 0.396 Ha is accepted, which means that there is a relationship between empathy and prosocial behavior of children with strong category.